Rola ilustracji w literaturze dziecięcej i jej psychologiczne uwarunkowania w rozwoju dziecka = The role of illustration in children`s literature and its psychological conditions in child development - Walak, Bogumiła (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article raises important issues of the role of illustrations in children`s literature and its psychological conditions. Shown are the issues relating to the child`s perception: his/her thinking, perception, imagination, emotions, aesthetic education, text being subordinated to the illustration, the influence of the humour in illustration on the child`s mood. The author examines the above-listed considerations on the basis of the various stages of child`s development.
Keywords: ilustracja książkowa; estetyka; artyzm; emocje; komizm w ilustracji; dobór ilustracji; imprinting; book illustration; aesthetics; artistry; emotions; humour in illustrations; choice of illustrations